ダイ44ジ ナンキョク チイキ カンソクタイ カンソク ケンキュウ ショウシュウカイ センヨウ カンソクセン ホウコク - 小達, 恒夫; オダテ, ツネオ; 工藤, 栄; クドウ, サカエ; 牛尾, 収輝; ウシオ, シュウキ; 谷村, 篤; タニムラ, アツシ; 平譯, 享; ヒラワケ, トオル; 福地, 光男; フクチ, ミツオ; et al. (2003)
P(論文) 「第44次南極地域観測隊観測研究小集会-専用観測船」を、平成14年10月15日、国立極地研究所講堂において開催した。本年度出発する第44次日本南極地域観測隊(the 44th Japanese Antarctic Research Expedition, JARE-44)において実施される、「専用観測船」による海洋観測参加者を中心に34名の参加者があった。本研究小集会では、「専用観測船」航海乗船者へJARE参加の心構え及び安全対策の説明が行われた。併せて、「専用観測船」での希望観測項目の詳細を打ち合わせ、観測スケジュールが改訂された。 A workshop on "Marine Science Program in the 44th Japanese Antarctic Research Expedition on a Charter Research Vessel" was held on 15th October 2002 at the convention hall of the National Institute of Polar Research with 34 participants. Most of the participants will join the research cruise organized by the 44th Japanese Antarctic Research Expedition (JARE-44) using a charter vessel. One of the purposes of this workshop is to give detailed information on the JARE system. At the same time, safety guidelines for the cruise were explained. In addition, the work schedule for the cruise was revised based on detailed requests from the participants. departmental bulletin paper